“Eventually it Just Hit Like a Tonne of Bricks:” Life After Homelessness Amongst Takatāpui/LGBTIQ+ People in Aotearoa New Zealand - Brodie Fraser; Elinor Chisholm; Nevil Pierse (International Journal on Homelessness, 2024)
Although Takatāpui/ lesbian, gay, bisexual, transgender, intersex, questioning, plus (LGBTIQ+) people are over-represented in homelessness statistics, there is limited qualitative research that explores the enduring effects of homelessness once they have attained housing stability. Using data from eight semi-structured interviews, we explore life after homelessness for Takatāpui/LGBTIQ+ people in Aotearoa, New Zealand. Results show the long-term ramifications of homelessness, stigma, and shame about having experienced homelessness, participants’ desire to “turn their lives around,” and their experiences of supporting others. These findings show that experiencing homelessness influences people’s lives long after they are housed.